2016
DOI: 10.4062/biomolther.2016.094
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Inhibits the Migration and Invasion of B16F10 Mouse Melanoma Cells through Inactivation of the PI3K/Akt Signaling Pathway

Abstract: Baicalein, a natural flavonoid obtained from the rhizome of Scutellaria baicalensis Georgi, has been reported to have anticancer activities in several human cancer cell lines. However, its antimetastatic effects and associated mechanisms in melanoma cells have not been extensively studied. The current study examined the effects of baicalein on cell motility and anti-invasive activity using mouse melanoma B16F10 cells. Within the noncytotoxic concentration range, baicalein significantly inhibited the cell motil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 44 publications
1
25
1
1
Order By: Relevance
“…MMP2/9 and Pgp were highly expressed in lungs of melanoma-bearing mice ( Figure 8D), which results in high invasiveness and high malignancy. 30 In this study, the antitumor efficacy of Ptx injection was worst, because B16F10 was resistant to Ptx ( Figure S5 and Table S1). 17 Inhaled PG-SG-Ptx showed better efficacy, which was partly attributed to the inhibition of Pgp by PG increasing the sensitivity of B16F10 to Ptx.…”
mentioning
confidence: 75%
“…MMP2/9 and Pgp were highly expressed in lungs of melanoma-bearing mice ( Figure 8D), which results in high invasiveness and high malignancy. 30 In this study, the antitumor efficacy of Ptx injection was worst, because B16F10 was resistant to Ptx ( Figure S5 and Table S1). 17 Inhaled PG-SG-Ptx showed better efficacy, which was partly attributed to the inhibition of Pgp by PG increasing the sensitivity of B16F10 to Ptx.…”
mentioning
confidence: 75%
“…The polymerase chain reaction (PCR) was carried out using the Mastercycler (Eppendorf, Hamburg, Germany) with the following primers: MMP‐2, (sense) 5′‐CTT CTT CAA GGA CCG GTT CAT‐3′, (antisense) 5′‐GCT GGC TGA GTA GAT CCA GTA‐3′; MMP‐9, (sense) 5′‐TGG GCT ACG TGA CCT ATG ACC AT‐3′, (antisense) 5′‐GCC CAG CCC ACC TCC ACT CCT C‐3′; TIMP‐1, (sense) 5′‐TGG GGA CAC CAG AAG TCA AC‐3′, (antisense) 5′‐TTT TCA GAG CCT TGG AGG AG‐3′; TIMP‐2, (sense) 5′‐GTC AGT GAG AAG GAA GTG GAC TCT‐3′, (antisense) 5′‐ATG TTC TTC TCT GTG ACC CAG TC‐3′; GAPDH, (sense) 5′‐CGG AGT CAA CGG ATT TGG TCG TAT‐3′, and (antisense) 5′‐AGC CTT CTC CAT GGT GGT GAA GAC‐3′. Conditions for the PCR were performed as previously described (Choi et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Choi, E. O. et al [15] found that baicalein significantly inhibits invasiveness and the cell motility of B16F10 mouse melanoma Cells within the noncytotoxic concentration range, which is associated with its tightening of tight junction (TJ). The facts were demonstrated by down-regulation of the claudin family of proteins and increase in transepithelial electrical resistance.…”
Section: Inhibiting the Proliferation And Invasionmentioning
confidence: 99%
“…Rui, X. et al [3] and Choi, E. O. et al [15] reported baicalein appears to suppress colorectal cancer cell migration and invasion by decreasing the expression of MMP-2 and MMP-9 via inhibition of the AKT signaling pathway.…”
Section: Introductionmentioning
confidence: 99%